A case of angioimmunoblastic T-cell lymphoma mimicking angioedema - He Zhao; Yun Xia; Fei Su; Liuqing Chen; Bin Hu (Discover Oncology)
Abstract Angioimmunoblastic T-cell lymphoma (AITL) is a rare and aggressive T-cell lymphoma that accounts for only 1% to 2% of all cases of non-Hodgkin lymphoma (NHL). It usually affects middle-aged to elderly men and is associated with fever, night sweats, weight loss, and lymphadenopathy. Approximately 50% of AITL cases have cutaneous manifestations. However, these are not specific. A middle-aged man presented with facial edema with shortness of breath, which was successively misdiagnosed as oral infection, drug dermatitis, and varicella. The fluctuating and nonspecific manifestations of AITL may complicate and delay the definitive diagnosis, thereby affecting treatment and prognosis. This article summarizes the clinical presentation, pathologic features, differential diagnosis, and treatment of this case, emphasizing the importance of lymph node examination in the development of angioedema.